Hubungan Pendidik Dan Peserta Didik Persepektif Imam Al-Ghazali - Maudiyah; Mohammad Haspi Rohyan; Moh. Faizin (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This article is motivated by the fact that the relationship between educators and students, from an Islamic educational perspective, is central to the success of a learning process based on the values of faith and noble morals. This research aims to understand the concept, function, and nature of educators, and how the ideal relationship between educators and students can be realized in accordance with Islamic educational principles. The method used is library research with a qualitative descriptive approach through analysis of various relevant literature. The results show that educators act as mu'allim, murabbi, and muaddib (leaders), who not only teach knowledge but also instill moral and spiritual values, thus creating a harmonious educational relationship with worship values that shape perfect human beings.